Unleashing the Potential: An Integrated Analysis of Human Resource and Marketing Strategies in Empowering East Java's Tourism SMEs - Hermawati, Adya; Sembhodo, Abimanyu Tuwuh (RSF Conference Series: Business, Management and Social Sciences, 2023)
This study examines the implementation of human resource management (HRM) and marketing strategies in small and medium-sized enterprises (SMEs) within East Java's tourism sector. The imperative for examination arises from the observation that tourism SMEs in Indonesia have not yet fully regained their pre-COVID-19 pandemic level of recovery. There is also a lack of holistic research of HRM and marketing strategies implementation in SMEs in the tourism sector in East Java. The research involves 1320 respondents from 440 tourism SMEs and utilizes the Path Analysis method. The findings highlight significant relationships between spiritual marketing, innovation culture, quality of work life, and rewards within SMEs. These factors positively influence the market orientation of SMEs, facilitating the development of products and services that meet market demands, enhance customer experiences, and foster competitive advantage. Additionally, the study reveals that the interplay of spiritual marketing, innovation culture, quality of work life, and rewards directly impacts individual performance, consequently leading to enhanced overall SME performance, as measured by marketing performance.This research contributes to the existing body of knowledge in business research, offering valuable insights into the current dynamics of tourism SMEs in the region. Moreover, it provides strategic solutions to address the decline in tourist arrivals post the COVID-19 pandemic.